Management of Non-Vitamin K Antagonist Oral Anticoagulants in the Perioperative Setting. (3rd September 2014) - Dincq, Anne-Sophie; Lessire, Sarah; Douxfils, Jonathan; Dogné, Jean-Michel; Gourdin, Maximilien; Mullier, François
Abstract : The field of oral anticoagulation has evolved with the arrival of non-vitamin K antagonist oral anticoagulants (NOACs) including an anti-IIa agent (dabigatran etexilate) and anti-Xa agents (rivaroxaban and apixaban). The main specificities of these drugs are predictable pharmacokinetics and pharmacodynamics but special attention should be paid in the elderly, in case of renal dysfunction and in case of emergency. In addition, their perioperative management is challenging, especially with the absence of specific antidotes. Effectively, periods of interruption before surgery or invasive procedures depend on half-life and keeping a permanent balance between bleeding and thromboembolic risks. In addition, few data regarding the link between plasma concentrations and their effects are provided. Routine laboratory tests are altered by NOACs and quantitative measurements are not widely performed. This paper provides a review on the management of NOACs in the perioperative setting, including the estimation of the bleeding and thrombotic risk, the periods of interruption, the indication of heparin bridging, the usefulness of laboratory tests before surgery or invasive procedure, and the time of resuming. Most data are based on expert's opinions.